Pemanfaatan Limbah Cair Tahu Sebagai Pembuatan Pupuk Organik Dengan Penambahan Bakteri Baik Pada Yakult, Gula, Dan Air Kelapa - Muthia Lailyana; Eka Cahya Muliawati (Institut Teknologi Adhi Tama Surabaya, 2022)
Tofu liquid waste is a white liquid with a thick texture derived from unused tofu production. Tofu liquid waste contains nitrogen, phosphorus, potassium, and protein, which are easily fermentable. It will pollute the environment and cause a bad smell if it is directly thrown away without prior processing. Therefore, tofu liquid waste was processed into organic liquid fertilizer. The purpose of this study was to determine the effect of fermentation time and sugar ratio on the levels of N, P, K The manufacture of liquid fertilizer involves a fermentation process by adding Yakult and EM-4 because both contain lactobacillus bacteria which can help the fermentation process. The sugar and coconut water were also added in a ratio of 1:0.075, 1:0.125, and 1:0.25. The process of liquid waste fermentation was carried out for 5 days, 10 days, 15 days, and 20 days. Fertilizers were tested using the Kjeldahl method for nitrogen (N) levels, spectrophotometry to determine phosphorus (P2O5) levels, and AAS (atomic absorption spectroscopy) for potassium (K2O) levels. The best levels of N, P, and K were produced from tofu waste with a fermentation process for 10 days by 0.662%, 1.133%, and 1.239%, respectively.